Origin of Dawnside Subauroral Polarization Streams During Major Geomagnetic Storms. Issue 4 (25th August 2022) - Lin, Dong; Wang, Wenbin; Merkin, Viacheslav G.; Huang, Chaosong; Oppenheim, Meers; Sorathia, Kareem; Pham, Kevin; Michael, Adam; Bao, Shanshan; Wu, Qian; Zhang, Yongliang; Wiltberger, Michael; et al.
Abstract: Solar eruptions cause geomagnetic storms in the near‐Earth environment, creating spectacular aurorae visible to the human eye and invisible dynamic changes permeating all of geospace. Just equatorward of the aurora, radars and satellites often observe intense westward plasma flows called subauroral polarization streams (SAPS) in the dusk‐to‐midnight ionosphere. SAPS occur across a narrow latitudinal range and lead to intense frictional heating of the ionospheric plasma and atmospheric neutral gas. SAPS also generate small‐scale plasma waves and density irregularities that interfere with radio communications. As opposed to the commonly observed duskside SAPS, intense eastward subauroral plasma flows in the morning sector were recently discovered to have occurred during a super storm on 20 November 2003. However, the origin of these flows termed "dawnside SAPS" could not be explained by the same mechanism that causes SAPS on the duskside and has remained a mystery. Through real‐event global geospace simulations, here we demonstrate that dawnside SAPS can only occur during major storm conditions. During these times, the magnetospheric plasma convection is so strong as to effectively transport ions to the dawnside, whereas they are typically deflected to the dusk by the energy‐dependent drifts. Ring current pressure then builds up on the dawnside and drives field‐aligned currents that connect to the subauroral ionosphere, where eastward SAPS are generated. The origin of dawnside SAPS explicated in this study advances our understanding of how the geospace system responds to strongly disturbed solar wind driving conditions that can have severe detrimental impacts on human society and infrastructure. Plain Language Summary: Solar eruptions of mass and magnetic field can trigger geospace storms. The most well‐known storm phenomenon is the aurorae in the Earth's high‐latitude upper atmosphere. Below the latitude of auroral boundary, that is, in the subauroral region, westward plasma flows from hundreds of m/s to a few km/s are often observed from afternoon to midnight during geomagnetically active periods. The fast plasma flows have important space weather effects due to their very large speed over a narrow latitudinal range. It was newly discovered that similar fast eastward plasma flows exist on the dawnside subauroral region during an extreme geomagnetic storm on 20 November 2003. However, the origin of the dawnside subauroral fast flow is still a mystery. This study demonstrates that the dawnside subauroral fast flow only occurs during very strong geomagnetic storms when the magnetospheric ions can be transported to and accumulate in the morning sector to build up plasma pressure and currents to generate the subauroral plasma flow in the ionosphere. This mechanism is important for us to understand how the geospace responds to geomagnetic storms, especially when the storm activity level is extremely high that it may have severe adverse effects on human society and infrastructure. Key Points: Dawnside subauroral polarization streams (SAPS) occur during the main and recovery phases of major geomagnetic storms Strong magnetospheric convection transports energetic ions to the dawnside and inner magnetosphere during major storms Substantial subauroral upward field‐aligned currents develop on the dawnside to drive the eastward SAPS